THE DEVELOPMENT OF MUSICAL ART IN SURKHANDARYA REGION AND THE ESTABLISHMENT OF THE TERMEZ STATE MUSICAL EDUCATIONAL INSTITUTION - Sabohat Alimova (American Journals, 2023)
Historically it is known that Surkhandarya region was under Bukhara Khanate in the past.The works of art that our ancestors left to us and that have come down to us,archaeological finds are a complete example of this.
Keywords: Among them are ”Shalola”, ”pleasure”,”beautiful”,”silver fiber”, Surkhan flowers and “bouquet”